Radiation Characteristics of 3D Resonant Cavity Antenna with Grid-Oscillator Integrated Inside - L. A. Haralambiev; H. D. Hristov (International Journal of Antennas and Propagation)
A three-dimensional (3D) rectangular cavity antenna with an aperture size of 80 mm × 80 mm and a length of 16 mm, integrated with a four-MESFET transistor grid-oscillator, is designed and studied experimentally. It is found that the use of 3D antenna resonant cavity in case of small or medium gain microwave active cavity antenna leads to effective and stable power combining and radiation. The lack of lateral cavity diffraction and radiation helps in producing a directive gain of about 17 dB and radiation aperture efficiency bigger than 75% at a resonance frequency of 8.62 GHz. Good DC to RF oscillator efficiency of 26%, effective isotropic radiated power (EIRP) of 5.2 W, and SSB spectral power density of −82 dBc/Hz are found from the measured data. The 3D antenna cavity serves also as a strong metal container for the solid-state oscillator circuitry.